Childhood cancer treatment: an adult comparison. Issue 2 (April 2008) - Styczynski, Jan
Age has an important prognostic impact in oncology. The distribution of cancer, as well as its biology, cytogenetics and therapy outcome vary between children and adults. Major advances in the treatment of childhood leukemia and other pediatric neoplasms have led to a striking improvement in survival over the last 30 years. With multiagent chemotherapy, currently almost 80% of children but only 40% of adults reach long-term remission in acute lymphoblastic leukemia. Survival has also increased for older adults, however 5-year survival rates have fallen for older adolescent and young adult (AYA) cancer patients. Reasons for this decline, termed the ''AYA cancer survival gap'', remain a challenge for all clinicians. Lessons obtained from pediatric oncology, especially from acute lymphoblastic leukemia, might contribute to significant progress in adults with cancer.